(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The present communication aims to highlight the trend of distribution of butterfly species in and around the protected forest areas of Kuldiha Wildlife Sanctuary (KWS), characterized with habitat heterogeneity with respect to vegetational assemblages, soil profiles and water bodies in comparison to butterfly diversity in other parts of India and neighbouring country. Butterfly diversity and distribution along with the seasonal gradients across three landscape areas, viz., LSE1, LSE2 and LSE3 were recorded at Kuldiha, Odisha, India using line transect. The method has generated baseline information relating not only to diversity, but also synchronization with vegetative growth coupled with phenological periodicity, and habitat heterogeneity of this aesthetically celebrated faunal component in a tropical deciduous evergreen forest landscape. A total of 95 species belonging to 63 genera and 5 families was encountered throughout the whole study period (Winter, 2015 to Summer, 2018) excepting the monsoon months. Post monsoon lepidopteran assemblage pattern was quite different from that of the pre-monsoon. Maximum diversity was observed in the LSE2, i.e. Mixed forest type exposed to certain levels of anthropogenic interactions. Present studies are considerably contribute to the ecobiology of the studied flagship species in particular and as a step towards holistic conservation strategy of an ecopotential sanctuary in the tropical country, India in general. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 93-104